Aspect of fiscal consolidation: Evidence from Serbia - Kalaš, Branimir; Andrašić, Jelena; Pjanić, Miloš (The European Journal of Applied Economics, 2016)
In contemporary market conditions facing continuous debt crisis, the notion of fiscal consolidation is one of potential solutions for solving the main economic issues in any country. As regards fiscal consolidation, it necessary to point out to the importance of developing strategies aimed at minimizing deficit and debt level. Serbia is among those countries in which irrational spending is widely present with unfavourable tendency regarding the aspect of production and consumption. Over the past 25 years, Serbia has spent much more than it has produced, which has led to large budget deficits and debt level. The aim is to point out to the concept of fiscal consolidation and its implementation in Serbia, while the subject of this paper is to present the package of measures and strategies defined by the government of the Republic of Serbia and the Fiscal Council Program.